Long term study of directly hybridized proton exchange membrane fuel cell and supercapacitors for transport applications with lower hydrogen losses. (April 2020) - Arora, D.; Bonnet, C.; Mukherjee, M.; Arunthanayothin, S.; Shirsath, A.V.; Lundgren, M.; Burkardt, M.; Kmiotek, S.; Raël, S.; Lapicque, F.; Guichard, S.
Highlights: Fuel cell directly hybridized with supercapacitor is realistic for FC hybrid vehicle. Direct hybridization is not detrimental to the FC durability. Direct hybridization allows to operate with reduced minimum gas flow rate. Reduced minimum gas flow rate is only sustainable in direct hybridization mode. Direct hybridization allows to decrease hydrogen waste. Abstract: Fuel cells (FC) and supercapacitors (SC) directly hybridized allow instantaneous response to peak energy demands in transportation applications. Under urban driving cycle, Fuel Cell Dynamic Load Cycling (FC_DLC), gases are fed with a minimum gas flow rate, corresponding to a safety limit current density (iSL ), inducing hydrogen oversupply. To reduce this oversupply, the present work focuses on iSL impact on the FC performance and durability. Two iSL conditions (0.2 and 0.05 A cm −2 ), were investigated under long-term FC_DLC runs with or without hybridization. At low iSL, hybridization allows 8% reduction in hydrogen oversupply; in addition, non-hybridized FC lifetime was found two-time shorter than that of hybridized FC. Erosion of the microporous layer of the gas diffusion layer (GDL) evidenced by scanning electron microscopy at the cathode, results in poorer water management, in consistence with the sudden voltage drops observed and the high increase in through-plane gas permeability in the GDL. Graphical abstract: Image, graphical abstract